Analisis Perlindungan Hukum bagi UMKM Tidak Berbadan Hukum di Kabupaten Kuningan - Audina Nursyifa; Bintang Nayla Aprillia; Fetty Dwiyutika (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the national economy, yet many MSME actors in Kuningan Regency still operate without formal legal entity status. This condition makes them vulnerable to legal risks, limits access to financing, and weakens their position in business agreements. This study aims to analyze the forms of legal protection available for non-incorporated MSMEs, the legal risks they face, and the government’s efforts to encourage business legalization. The research employs a socio-legal approach and qualitative case study method through interviews with three MSME actors: Mandiri Food, CV Highland Bakery, and PT Windu Mulia Transport. The results indicate that although MSME actors recognize the importance of legal status, limited financial resources and lack of information remain major obstacles. The government has provided various facilitation programs for legalization, yet they have not reached all MSME actors evenly. Greater efforts are needed in education, assistance, and legal support to ensure MSMEs grow legally and sustainably.